2018
DOI: 10.4269/ajtmh.17-0771
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Norovirus and Attitudes toward a Potential Norovirus Vaccine in Rural Guatemala: A Cross-Sectional Exploratory Survey

Abstract: Given limited data on norovirus vaccine acceptance, we performed an exploratory survey in a rural Guatemalan community on knowledge, interest, and willingness to pay (WTP) for a norovirus vaccine. Cluster-randomized households with children aged 6 weeks to 17 years were enrolled into one of two norovirus surveillance studies: 1) a prospective cohort ( = 207 households) and 2) two separate, community-based, cross-sectional surveys ( = 420 households). After completion of the surveillance study, vaccine surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that low parental health literacy correlates with worse health outcomes in their children [25,26]. Good knowledge about virus infection in the general public will help to reduce the health consequences of virus infection and to increase the population's willingness to pay for future vaccination [24,27]. This present study demonstrates that parents whose children attended kindergartens had poor awareness of HuNoV infection in Chengdu.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies revealed that low parental health literacy correlates with worse health outcomes in their children [25,26]. Good knowledge about virus infection in the general public will help to reduce the health consequences of virus infection and to increase the population's willingness to pay for future vaccination [24,27]. This present study demonstrates that parents whose children attended kindergartens had poor awareness of HuNoV infection in Chengdu.…”
Section: Discussionmentioning
confidence: 53%
“…One Guatemalan study, conducted in 2017, assessed attitudes toward a potential norovirus vaccine and found respondent attitudes to be generally positive, except among those with prior history of vaccine refusal. 8 With advances in both pediatric, 9 and adult clinical trials, 10 it is an opportune time to explore attitudes about a potential norovirus vaccine in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Guatemala is one such country with a history of inconsistent vaccine access and high vaccine acceptance, though vaccine hesitancy in certain populations has been increasing, especially during the COVID-19 pandemic [ 9 , 10 , 11 , 12 , 13 ]. Guatemala’s health system is composed of two sectors, public and private.…”
Section: Introductionmentioning
confidence: 99%